Executive function training curriculum to enhance emotional intelligence in early childhood: Theory adaptation in educational design research - Pumyoch, Natthiya; Srikoon, Sanit (Thinking skills and creativity, 2024)
•Developed Executive Function Training (EFT) Curriculum in early childhood.•Implementing educational research design (EDR) to design and develop an EFT curriculum.•Adapt the construction of Wongwanich's (2020) design principal approach to McKenney and Reeves's (2019) EDR as a more challenging theory construction in EDR.•Focus on advancing EFT curriculum development methodology through the theory adaptation of EDR in early childhood.•Provided new theory construction into EFT curriculum's application in early childhood classroom challenges. Emotional intelligence (EI) is vital for early childhood development and is closely linked to executive function (EF). EF is a foundation of cognitive ability in early childhood. Educational design research (EDR) offers an adaptive methodology for curriculum development. This study aimed to (1) analyze and explore perspectives for designing an executive function training (EFT) curriculum to enhance EI, (2) design and develop the EFT curriculum, and (3) evaluate and reflect on the EFT curriculum. The research underscores the need to enhance EI, social skills, self-help abilities, and positive attitudes in early childhood students. Developed through a collaborative effort involving multiple stakeholders, the EFT curriculum aligns with Thailand's Ministry of Education standards. It significantly improves EI scores across six assessments of EI's five elements: self-awareness, self-regulation, motivation, empathy, and adeptness in relationships. The EFT curriculum emphasizes inhibitory control, shift/cognitive flexibility, emotional control, working memory, planning/organizing, and incorporating sleep to support cognitive and emotional development, a total of 150 hours. Developed with stakeholder input and rigorous design principles, the EFT curriculum prepares children for future learning and life challenges.